Job Boredom, Work Overload, dan Cyberloafing: Uji Peran Mediasi Rumination dan Job Stress Pada Karyawan Generasi Milenial - Prabaratri, Lintang; Ekowati, Dian (Jurnal Maksipreneur, 2024)
Internet usage at the workplace has the potential for misuse with employees engaging in cyberloafing activities. Therefore, this research was conducted to examine the relationship between job boredom and work overload on cyberloafing with the mediation of rumination and work stress. This research uses quantitative methods and respondents were selected using a purposive sampling technique, namely workers belonging to the millennial generation and working using internet technology from various industrial sectors, totaling 311 respondents. The data testing technique used is SmartPLS 3.2.9 software. There are five hypotheses accepted out of eight hypotheses in total. Excessive workload has a negative and significant effect on cyberloafing. Work boredom has a positive and significant correlation with rumination. Meanwhile, workload has a negative and significant influence on work stress. Rumination has a positive but not significant relationship with cyberloafing. Job stress has a positive and significant effect on cyberloafing. Meanwhile, for the mediation results, it was found that work boredom had a negative and significant effect on cyberloafing if mediation was carried out with rumination. Excessive workload has a positive but not significant correlation with cyberloafing if mediated by work stress.